Model Matematika dan Simulasi Untuk Non-Idealitas Reaktor Alir Pipa - Gunarto Gunarto (Eksergi, 2008)
This paper presents a mathematical model for the performance of a non-ìdeality plugflow reactor. An analytical technique used was the residence time distribution (RTD) involving tracer component. This model can give a prediction of the number of the ideal continuous stirred tank reactors that could represent the non-ideal plug flow reactor. Regardíng to the literature, the result obtained is 9 continuous stirred tank reactors in series would represent the performance of non-ideal plugflow reactor that was analyzed